Research on the Social Safety Valve Function of the Stigma towards Studying Abroad - Hu, Yifan (Transactions on Social Science, Education and Humanities Research, 2024)
There is no lack of research on stigma and international students in China, but little research has been done on the stigma experienced by Chinese Students Studying Abroad for a Master’s Degree. Through semi-structured interviews with domestic groups and overseas masters, the study explores the sources and functions of stigma in the context of the social safety valve. The study found that the stigma of masters studying abroad is homogenized by the domestic community due to the fermentation of the "craze for studying abroad" and the "return to China" wave. Through the stigma, the domestic community has resolved their dissatisfaction and anxiety, and master’s degree holders have achieved the positive function of the social safety valve by reducing the high expectations they have to bear.